Evaluation of changes in skin biophysical parameters and appearance after pneumatic injections of non-cross-linked hyaluronic acid in the face. (17th November 2018) - Cheng, Hai-yan; Chen, Yu-xin; Wang, Mei-fang; Zhao, Jun-ying; Li, Lin-feng
ABSTRACT: Background : Pneumatic injections of non-cross-linked hyaluronic acid are effective in skin rejuvenation, however, the associated biophysical parameters and appearance have not been evaluated.Objectives : To determine the changes in skin biophysical parameters after facial pneumatic injections of non-cross-linked hyaluronic acid.Patients and methods : Twenty-eight healthy female volunteers received pneumatic injections of non-cross-linked hyaluronic acid into the face for consecutive 5 weeks. Skin biophysical parameter assessment and clinical evaluation were performed using the CK Multi-Probe Adapter and Visia system. Five of the volunteers also underwent retroauricular skin biopsy before and after the last treatment. The skin tissues were all stained with Masson-trichrome, Verhoeff-van Gieson stain, and hematoxylin-eosin to evaluate the changes in collagen, elastic fibers, and the epidermis, before and after the last treatment.Results : Transepidermal water loss was significantly lower in week 4 (18.46 ± 4.70 g/h/m 2 ) than at the baseline (22.03 ± 7.15 g/h/m 2, p < 0.05). Skin texture was better in week 4 (599.29 ± 354.32) than at the baseline (668.43 ± 342.55, p < 0.05). Skin pores also improved significantly at week 4 (934.07 ± 458.78) compared to the baseline (1024.57 ± 415.31, p < 0.05). Skin wrinkles were improved at the 3-month follow-up (29.29 ± 11.11) compared to the baseline (35.83 ± 16.05, p < 0.05).Conclusion : Pneumatic injections of non-cross-linked hyaluronic acid improved skin TEWL, texture, pores, and wrinkles.